2004
DOI: 10.1053/j.gastro.2004.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a new human CYP1A1 regulation pathway involving PPAR-α and 2 PPRE sites

Abstract: We describe here a new cytochrome P450 1A1 induction pathway involving peroxisome proliferator-activated receptor-alpha and 2 peroxisome proliferator response element sites, indicating that peroxisome proliferator-activated receptor-alpha ligands, which are common environmental compounds, may be involved in carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Collectively, these results provide a possible mechanism for AhR and BMAL1 to regulate PPAR-α. Because PPAR-α regulates BMAL1, AhR, and CYP1A1 (Canaple et al 2006; Seree et al 2004; Villard et al 2007), we speculate that the inhibitory effect of Bmal1 silencing on AhR and CYP1A1 may be mediated by PPAR-α. Similarly, the reduction in BMAL1 caused by Ahr silencing may depend on PPAR-α.…”
Section: Discussionmentioning
confidence: 93%
“…Collectively, these results provide a possible mechanism for AhR and BMAL1 to regulate PPAR-α. Because PPAR-α regulates BMAL1, AhR, and CYP1A1 (Canaple et al 2006; Seree et al 2004; Villard et al 2007), we speculate that the inhibitory effect of Bmal1 silencing on AhR and CYP1A1 may be mediated by PPAR-α. Similarly, the reduction in BMAL1 caused by Ahr silencing may depend on PPAR-α.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the analysis of ROS and steroid biosynthesis revealed that ROS generated by MEHP affects testicular steroidogenesis via the Cyp1a1 gene and its gene network. Activation of the PPAR family of transcription factors by MEHP could target the two PPAR response elements in the Cyp1a1 gene (78). The mechanism by which MEHP acts to inhibit steroidogenesis in MA-10 cells might apply more broadly because a number of endocrine disruptors in the environment generate ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several nuclear receptors are involved in the upregulation of hCYP1A1 ; for example, the constitutive androstane receptor (CAR) [37] which is also a regulator of the expression of the CYP2A, 2B, 2C, and 3A subfamilies is activated by drugs; the liver X receptor α (LXR α ) that is involved in lipid homeostasis is activated by oxysterols [38, 39]; and the peroxisome proliferator-activated receptor α (PPAR α ), is activated by fibrates, phthalates, arachidonic acid, and its derivatives [40, 41]. These receptors bind to their specific responsive elements located in the gene promoter, activate the transcription, and potentiate the induction of hCYP1A1 .…”
Section: Upregulation Of Cyp1a1mentioning
confidence: 99%